A P/N/S-containing compound toward enhanced fire safety epoxy resin with well-balanced performance. (October 2021) - Wan, Chao; Duan, Huajun; Zhang, Chenhao; Cao, Jianfan; Zou, Jiahao; Zhang, Junjun; Ma, Huiru
Highlights: A flame retardant containing P/N/S was synthesized. STP improved fire safety and mechanical performance of EP. Tg of FREP was higher than EP after adding a certain amount of STP. Transparency and thermal stability of FREP were not sacrificed. Abstract: In order to obtain an efficient flame retardant without sacrificing mechanical properties and transparency of epoxy resin (EP), a P/N/S-containing flame retardant (STP) by combining 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) with Schiff base intermediate synthesized by the reaction of sulfathiazole and 2-thenaldehyde was successfully synthesized. The synthesis of STP was verified and the properties of modified EP were studied. The test results indicated that STP slowed down the degradation rate of EP. The glass transition temperature (Tg ) of the flame-retardant epoxy resin (FREP) samples were well maintained and even improved after introducing a certain amount of STP. Furthermore, FREP with low phosphorus content exerted excellent flame retardant ability, EP/5%STP (phosphorus content: 0.27 wt%) obtained the V-0 rating of UL-94 test with the value of limiting oxygen index (LOI) 33.5%. In contrast with EP, the peak heat release rate (PHRR), total heat release (THR) and total smoke production (TSP) of EP/7.5%STP were respectively decreased by 33.31%, 26.04% and 28.75%. Mechanical performance tests show that STP improved the tensile and flexural strength of EP. It is worth mentioning that the EP modified with STP still maintains good transparency.